Switching banks: gone but not forgotten - Garland, Ron (Henry Stewart Talks, 2008)
Fresh insights into bank switching, Brand switching perspectives from FMCG sector applied to bank brand switching, Who are the bank switchers?, Reasons for switching, Answers to the basic 'customer recovery' question: 'now that you have a new bank, what are the chances of you resuming business with your old bank?'